Asymmetric de novo synthesis of fluorinated D-glucitol and D-mannitol analogues - Giuffredi, G; Purser, S; Sawicki, M; Thompson, A; Gouverneur, V (2009)
A highly efficient anti-SE2′ electrophilic fluorination of enantioenriched allylsilanes a subsequent dihydroxylation of the resulting allylic fluorides were used as key steps for the synthesis of three fluorinated carbohydrate analogues, 1,5-di-O-benzyl-2-deoxy-2-fluoro-d-glucitol, 2,6-di-O-benzyl-5-deoxy-5-fluoro-l-glucitol and 1,5-di-O-benzyl-2-deoxy-2-fluoro-d-mannitol. A new catalytic asymmetric route to 1-benzyloxy-4-trimethylsilyl-but-3-yn-2-ol, a common precursor to two advanced allylsilanes, is also described featuring a Noyori asymmetric transfer hydrogenation reaction. © 2009 Elsevier Ltd. All rights reserved.